Effects of Dietary Supplementation of Essential Oils as an Alternative to Antibiotic Growth Promoter on Performance of Commercial Broilers - C, Rajalekshmi; Mishra, Ram Kailash; Savaliya, Fulabhai P; Patel, Atul B; Lunagariya, Pravin M; Bhagora, Nitesh J (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
An experiment was conducted to assess the effects of thyme and peppermint essential oils (EO) as an alternative to antibiotic growth  promoter (AGP) on the performance of broiler chicken. Total 256 day-old Vencobb broiler chicks were randomly distributed into eight  experimental groups with four replicates of eight birds each. Experimental groups were fed with control diet without supplementation  of AGP and essential oils (T1), BMD (Bacitracin Methylene Disalicylate) antibiotic @ 500 mg/kg diet (T2), thyme essential oil @ 150 mg/kg  diet (T3), 200 mg/kg diet (T4), 250 mg/kg diet (T5), peppermint essential oil @ 200 mg/kg diet (T6), 250 mg/kg diet (T7) and 300 mg/kg  diet (T8). The supplementation of thyme oil @ 200 mg/kg and peppermint oil @ 300 mg/kg broiler diet significantly (p
Keywords: AGP; Broiler performance; Essential oil; Thyme; Peppermint